Public Libraries: Community Fountain of Inforamtion Education and Culture - Deshapande, K. S. (Journal of Information and Knowledge, 2000)
Democracy can succeed only in an enlightened society. An Enlightened Socity requires proper education, both formal and non-formal to its citizenry. The non-formal education can only be provided with a strong network of public libraries. The paper discusses the importance of public libraries especially in a developing country like Inida. An example of Family Planning Association of India is given to illustrate how its experience in acting as an information centre in promoting the ideals of a small family using varieties of information in varied ways can be followed by public libraries. It also suggests the public libraries to ensure help from other departments in providing information.